Tingkat pemahaman peserta didik kelas X terhadap materi permainan bola voli melalui pembelajaran daring di SMA negeri 1 pengadang - Nurtajudin; Adi Suriatno (Jurnal Pengetahuan dan Pendidikan, 2026)
Online Physical Education, Sports, and Health learning presents several limitations because volleyball instruction requires not only theoretical knowledge but also an understanding of movement techniques, rules, facilities, and equipment. This study aimed to determine the level of tenth-grade students’ understanding of volleyball learning materials delivered through online instruction. This study employed a quantitative descriptive approach using a survey method. The research sample consisted of 50 students selected through proportional random sampling. Data were collected using a one-shot technique through a multiple-choice test distributed via Google Forms. The initial instrument consisted of 30 items, of which 25 items were declared valid after validity testing. The reliability test produced a coefficient of 0.638, which was higher than the r-table value of 0.279; therefore, the instrument was considered reliable. The data were analyzed using descriptive statistics involving frequency, percentage, mean, and standard deviation. The results indicated that the students’ overall understanding of volleyball learning materials was categorized as high. Regarding the ability to identify basic volleyball techniques, 74% of the students were in the high category. The percentages in the high category were 44% for interpreting basic techniques, 42% for integrating prior knowledge with the material presented by the teacher, and 46% for explaining basic movements. For the indicator related to rules, facilities, and equipment, the largest proportion of students was in the moderate category, accounting for 48%. In conclusion, the students demonstrated a good understanding of volleyball learning materials, although their understanding of rules, facilities, and equipment still needs improvement.